Pembelajaran Operasi Perkalian Menggunakan Metode Jarimatika dan Lidimatika - Nasrul Naufal; Siti Kurnia; Aulia Khairunnisa; Lia Halimatus Sadiah; Nurul Hidayati; Chelsi Ariati; Hanne Ayuningtias Elsa; Suhendra (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
The multiplication operation is a crucial topic in learning mathematics. Nevertheless, there were still students who considered the topic to be a difficult topic, one of which was for elementary and junior high school students at the Graha Asuh Jabal 165 Foundation, Bandung Regency. These problems occur due to the learning process that is not optimal. Therefore, the purpose of carrying out this service activity is to help students or service targets understand the concept on the topic of multiplication operations which are packaged in an attractive way so that students are motivated to take part in the learning process. The method for implementing this activity consists of three stages, namely: (1) the activity planning stage; (2) implementation stage; and (3) evaluation stage. The results obtained in this service activity are in the form of student responses which indicate that students are very enthusiastic in participating in the learning process, and make it easy for students in the process of calculating multiplication operations.